RANCANG BANGUN JEMURAN OTOMATIS MENGGUNAKAN ARDUINO UNO DAN MIKROKONTROLER - Bustommy Saputra; Bosar Panjaitan (FAKULTAS TEKNIK, 2021)
When the rainy season, the majority of people feel anxious when they are drying their clothes. The anxiety will increase when drying clothes, especially when the person is going to travel and when no one at home. From this incident, people are reluctant to dry clothes in the open, because they are worried that the clothesline will get wet with rain water when the owner leaves them when they are outside the house. The goal of this research is to design an automatic clothesline that can inserting and removing clothespinswithout being done by humans. By designing all tools ranging from a raindrop sensor to detect rainwater and a raindrop sensor that is specifically for detecting wet or dry clothes placed on hungers and motorbikes. servo as an activator for inserting and removing clothespins.The result of this research is an automatic clothesline that is useful for dealing with putting clothes in when it rains, or putting clothes that are dry so that people feel safer with clothes that are dried in the sun and feel safer with the rain.